2019
DOI: 10.3906/elk-1807-41
|View full text |Cite
|
Sign up to set email alerts
|

Lexicon-based emotion analysis in Turkish

Abstract: In this paper, we proposed a lexicon for emotion analysis in Turkish for six emotional categories happiness, fear, anger, sadness, disgust, and surprise. Besides, we also investigated the effects of a lemmatizer and a stemmer, two term-weighting schemes, four lexicon enrichment methods, and a term selection approach for lexicon construction. To do this, we generated Turkish emotion lexicon based on a dataset, TREMO, containing 25,989 documents. We then preprocessed the documents to obtain dictionary and stem f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Lexicon-based sentiment analysis uses preconstructed emotional lexicons for determining the polarity of textual content (Turney, 2002). Each text is searched for revealing emotional terms given in the lexicon and then weights are assigned to each of those terms (Toçoğlu and Alpkocak, 2019). Lexicon-based classification does not need to be labeled data, but it is difficult to create a unique lexically based dictionary to be used for different contexts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lexicon-based sentiment analysis uses preconstructed emotional lexicons for determining the polarity of textual content (Turney, 2002). Each text is searched for revealing emotional terms given in the lexicon and then weights are assigned to each of those terms (Toçoğlu and Alpkocak, 2019). Lexicon-based classification does not need to be labeled data, but it is difficult to create a unique lexically based dictionary to be used for different contexts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To annotate tweets, we have intensively used TEL, which consists of 7,235 keywords, in total, for six emotion categories of fear, happy, disgust, anger, sadness, surprise [36]. Table 1 shows sample keywords selected from TEL for each emotion category, where English translations are presented in italic.…”
Section: B Curation Of Datasetmentioning
confidence: 99%
“…For annotation, we performed a lexicon-based automatic annotation process using TEL [36], which includes keywords lemmatized by TurkLemma [38]. Then, we annotated each tweet with a category name of a TEL keyword contains in that tweet.…”
Section: B Curation Of Datasetmentioning
confidence: 99%
“…In the experiments performed on TREMO, the highest performance was achieved with the SVM with an 86% general accuracy. In the continuation study [32], an emotion lexicon was produced using TREMO, and lexicon-based emotion analysis was performed. The lexicon-based approach proposed in the study showed competitive performance against the TML methods with an accuracy of 91%.…”
Section: Introductionmentioning
confidence: 99%